2008
DOI: 10.1002/ejic.200700971
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of para‐Amino Benzoic Acid–TiO2 Hybrid Nanostructures of Controlled Functionality by an Aqueous One‐Step Process

Abstract: In situ amino acid surface-modified TiO 2 nanoparticle syntheses were performed by a simple one-pot hydrolysis of heteroleptic titanium alkoxide [Ti(OiPr) 3 (O 2 CC 6 H 4 NH 2 )] m in water with N n Bu 4 Br. This process allowed precise control of the surface grafting rate by varying the amount of precursors and provided highly functionalized nanomaterials. Their compositions and microstructures were determined by C, H and N elemental analyses, TGA-MS, 13 C CP-MAS NMR, XRD, TEM, BET, Raleigh diffusion, FTIR, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 70 publications
(20 reference statements)
3
19
0
Order By: Relevance
“…Pure TiO 2 only shows a broad weight loss of 17% from room temperature to 420 °C, which is assigned to water, ethanol, ethylacetoacetate (EtAcAc), and possibly isopropanol from unreacted TiO 2 precursors [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure TiO 2 only shows a broad weight loss of 17% from room temperature to 420 °C, which is assigned to water, ethanol, ethylacetoacetate (EtAcAc), and possibly isopropanol from unreacted TiO 2 precursors [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second step from 120 to 250 °C only shows a minor weight loss of 3% and is likely due to evaporation of more strongly bonded water and ethanol. The third step with an overall weight loss of 20% can again be assigned to silk degradation and combustion of unreacted EtAcAc and TTIP occurring between 250 and 600 °C [ 82 ]. No further weight loss is observed up to 1000 °C and the residual 68% can be assigned to TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The side-view of CuTPP, which has a perfect planar structure, is also presented as a reference. [22] In ZnTPP-AOP, the Zn 2+ is 0.2400(17) Å above the porphyrin ring. The porphyrin ring is twisted to a small extent, which becomes more severe in H 2 TPP-AOP.…”
Section: Snthesis and Structural Characterizationmentioning
confidence: 99%
“…[32] (sample with 20% in weight of PABA) and the same batch was used for all the experiments. NEt 3 , N,N 0 -dicyclohexylcarbodiimide (DCC), Ln(NO 3 ) 3 ,6H 2 O (Ln = La, Gd) and anhydrous DMF, CH 2 Cl 2 were purchased from Sigma-Aldrich and used as received.…”
Section: Chemicals and Analysismentioning
confidence: 99%
“…Silica-based (nano) materials were mainly used because of the stability of the inorganic component under c-irradiation, of the large availability of R-Si(OR') 3 precursors and of the elaboration of highly stable hybrid networks due to strong SiAC bond [31]. Non silicate systems as selective extracting technologies were poorly studied because of the need of a reliable and reproducible functionalization route as we previously reported [32][33][34]. Li et al reported the immobilization of lanthanides (III) on an iso-nicotinic acid functionalized titania material in order to study the luminescence properties of these hybrid materials [35,36].…”
Section: Introductionmentioning
confidence: 97%